Analisis Wacana Kritis Model Teun A. Van Dijk pada Roasting Kiki Syahputri terhadap Para Menteri Kabinet Republik Indonesia - Ira Annisa Purawinangun; Yumna Rasyid; Miftahulkhairah Anwar (Ksatra: Jurnal Kajian Bahasa dan Sastra, 2022)
This study discusses Kiki Syahputri's roasting video broadcast on Youtube with the title "Pecah!!! Kiky Saputri Roasting Jokowi's Ministers, All Do Not Move ". The purpose of this study is to analyze the elements of discourse using the Teun A. Van Dijk model on Kiki Syahputri's roasting show that aired on Youtube media with the title "Break!!! Kiky Saputri Roasting Jokowi's Ministers, All Do Not Move ". The research method used in this research is descriptive qualitative. The data analysis technique used by the researcher is using content analysis. The technique used in data collection is the note-taking technique. Based on the results of the study, it can be concluded that there are four elements with different sub-analyses. Among them are semantic elements (background, details, intent) which discuss in more detail the meaning that you want to emphasize in a discourse. Next is the syntactic elements (sentence forms, pronouns, stylistics, and rhetorical) which are used to analyze the form or arrangement of sentences used by Kiky Saputri and see how the emphasis is done by using the inclusion of images, word order in the title, bolding letters, italics, quotes, and so on within the cover of the video that airs on the YouTube channel.